The Insulin Receptor Substrate 1 (Irs1) in Intestinal Epithelial Differentiation and in Colorectal Cancer - Esposito, Diana L.; Aru, Federica; Lattanzio, Rossano; Morgano, Annalisa; Abbondanza, Michela; Malekzadeh, Reza; Bishehsari, Faraz; Valanzano, Rosa; Russo, Antonio; Piantelli, Mauro; Moschetta, Antonio; Lotti, Lavinia Vittoria; et al. (PLOS ONE, 2012)
Colorectal cancer (CRC) is associated with lifestyle factors that affect insulin/IGF signaling, of which the insulin receptor substrate 1 (IRS1) is a key transducer. We investigated expression, localization and pathologic correlations of IRS1 in cancer-uninvolved colonic epithelium, primary CRCs with paired liver metastases and in vitro polarizing Caco2 and HT29 cells. IRS1 mRNA and protein resulted higher, relative to paired mucosa, in adenomas of familial adenomatous polyposis patients and in CRCs that overexpressed c-MYC, ß-catenin, InsRß, and IGF1R. Analysis of IRS1 immunostaining in 24 cases of primary CRC with paired colonic epithelium and hepatic metastasis showed that staining intensity was significantly higher in metastases relative to both primary CRC (P<0.01) and colonic epithelium (P<0.01). Primary and metastatic CRCs, compared to colonic epithelium, contained significantly higher numbers of IRS1-positive cells (P = 0.013 and P = 0.014, respectively). Pathologic correlations in 163 primary CRCs revealed that diffuse IRS1 staining was associated with tumors combining differentiated phenotype and aggressive markers (high Ki67, p53, and ß-catenin). In Caco 2 IRS1 and InsR were maximally expressed after polarization, while IGF1R was highest in pre-polarized cells. No nuclear IRS1 was detected, while, with polarization, phosphorylated IRS1 (pIRS1) shifted from the lateral to the apical plasma membrane and was expressed in surface cells only. In HT29, that carry mutations constitutively activating survival signaling, IRS1 and IGF1R decreased with polarization, while pIRS1 localized in nuclear spots throughout the course. Overall, these data provide evidence that IRS1 is modulated according to CRC differentiation, and support a role of IRS1 in CRC progression and liver metastatization.